2018
DOI: 10.2174/1574886313666180619120406
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of Drugs and Adverse Drug Reactions in Pediatric Units: A Prospective, Multicenter Study

Abstract: The present study indicates that children admitted to neonatal intensive care units are likely to receive an off-label medication; children who receive an off-label medication are usually more likely to be treated with more medication than the others; adverse drug reactions occur in patients admitted in neonatal intensive care and pediatrics are units are more frequently with off-label than with on-label drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 0 publications
0
82
0
2
Order By: Relevance
“…16 Given the potential for increasing the rate of pediatric approvals in at least part of the pediatric population at the time of adult drug approvals, the experience of the FDA with combined pediatric and adult trials is particularly valuable. The objectives of this evaluation were (1) to perform a review of the BPCA and/ or PREA and orphan drug submissions to the FDA where combined adult and pediatric trials were conducted, (2) to evaluate the most relevant therapeutic areas in which combined trials were conducted, (3) to identify the trials that reported separate safety and efficacy analyses for the pediatric subgroups, and (4) to delineate which dosing methods were most often utilized in the combined trials.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…16 Given the potential for increasing the rate of pediatric approvals in at least part of the pediatric population at the time of adult drug approvals, the experience of the FDA with combined pediatric and adult trials is particularly valuable. The objectives of this evaluation were (1) to perform a review of the BPCA and/ or PREA and orphan drug submissions to the FDA where combined adult and pediatric trials were conducted, (2) to evaluate the most relevant therapeutic areas in which combined trials were conducted, (3) to identify the trials that reported separate safety and efficacy analyses for the pediatric subgroups, and (4) to delineate which dosing methods were most often utilized in the combined trials.…”
Section: Articlementioning
confidence: 99%
“…Additional information regarding clinical studies was also retrieved from ClinicalTrials.gov and journal publications indexed on PubMed/Medline. This study did not require Research Involving Human Subjects Committee review and approval under 45 Code of Federal Regulation (CFR) §46.101b (4).…”
Section: Data Sourcesmentioning
confidence: 99%
“…опубликовали данные о значительном увеличении риска побочных эффектов (отношение рисков 1,28; 95% доверительный интервал 0,43-3,78; p=0,002) [13]. Напротив, частота побочных реакций в большом многоцентровом проспективном исследовании педиатрических отделений составила 36,7% для «off-label use» против 63,3% для препаратов, назначаемых согласно утвержденной инструкции [14], что можно объяснить весьма взвешенным подходом врача к рекомендациям такого рода. Г.В.…”
Section: «Off-label» назначения лекарственных средств в практикеunclassified
“…The frequent off-label prescribing of medications in this population 2 makes them particularly vulnerable to ADRs. 3,4 Children with chronic neurologic conditions are particularly at risk of ADRs because of underlying conditions and the high frequency of polypharmacy. 2,5 The highest rate of fatalities due to antiepileptic drugs (AEDs) have been reported to occur in children.…”
Section: Introductionmentioning
confidence: 99%